2012
DOI: 10.1016/j.tig.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The resurgence and genetic implications of New World primates in biomedical research

Abstract: There has been a recent resurgence of interest in New World monkeys within the biomedical research community, driven both by the sequencing of the common marmoset (Callithrix jacchus) genome as well as a growing demand for alternatives to Old World primates. New World monkeys offer attractive advantages over Old World species including cheaper and simpler husbandry while still maintaining a greater evolutionary proximity to humans than other animal models. Although numerous commonalities across primate species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…The Neotropical primates have an important role regarding the phylogenetic proximity with the human being, which, due to their size and easy handling, are currently important models for biomedical research (Ward and Vallender, 2012). The availability of these animals is certainly one of the main contributors to the rise of Brazil in the international community of biomedical research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Neotropical primates have an important role regarding the phylogenetic proximity with the human being, which, due to their size and easy handling, are currently important models for biomedical research (Ward and Vallender, 2012). The availability of these animals is certainly one of the main contributors to the rise of Brazil in the international community of biomedical research.…”
Section: Introductionmentioning
confidence: 99%
“…With the growing demand of these animals, the search for biological information of the species has increased significantly since the anatomy to clinical medicine, enabling the permanence in captivity and expanding information bases for interpretations of experiments (Ward and Vallender, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…New World primates, including owl monkeys, are well-established models of human disease in biomedical research (41). This is in part due to the fact that most New World species are relatively small in body size and have rapid reproduction rates which facilitate the maintenance of productive breeding colonies.…”
Section: Discussionmentioning
confidence: 99%
“…However, phylogenetic analyses of MHC class I alleles in new world primates including marmosets and tamarins demonstrate that MHC class I genes cluster in a manner that is distinct from those of old world primates or humans (Adams and Parham, 2001;Watkins et al, 1993), and show an 82% identity with corresponding human leukocyte antigen (HLA; human equivalent of MHC) alleles in humans (Robinson et al, 2015;Cadavid et al, 1997;Shiina et al, 2011). New world primates also demonstrate reduced allelic MHC variability in the antigen binding domains compared to that found in old world primates and humans (Ward and Vallender, 2012;Cadavid et al, 1997;Otting et al, 2002). Further, detailed comparisons have demonstrated that MHC class II families in new world primates are not orthologous to those of old world primates and that these gene families may have evolved independently in new and old world primates (Kriener et al, 2001).…”
Section: Comparative Sequence Identity Of the Major Histocompatibilitmentioning
confidence: 99%
“…New world primates, such as marmosets, have practical advantages over old world primates as research models, including cost, size and generation time (Ward and Vallender, 2012). However, phylogenetic analyses of MHC class I alleles in new world primates including marmosets and tamarins demonstrate that MHC class I genes cluster in a manner that is distinct from those of old world primates or humans (Adams and Parham, 2001;Watkins et al, 1993), and show an 82% identity with corresponding human leukocyte antigen (HLA; human equivalent of MHC) alleles in humans (Robinson et al, 2015;Cadavid et al, 1997;Shiina et al, 2011).…”
Section: Comparative Sequence Identity Of the Major Histocompatibilitmentioning
confidence: 99%